Pengaruh Perbedaan Penggunaan Lajur Terhadap Karakteristik Arus Lalu Lintas Pada Ruas Jalan Slamet Riyadi Surakarta - Arifin, Muhammad Zainul; , Nurul Hidayati, ST., MT., Ph.D; , Ika Setiyaningsih, ST, MT (2016)
The development of IPTEK became the basis of increasing development in various fields which affect the transportation infrastructure needs. This resulted in the volume of traffic on a road becomes increasingly dense. The issue is considered from a buildup of traffic on a road or intersection, which is like a long queue and the convoy is very solid. When this happens then the need for proper traffic arrangements so that such problems can be solved. In this study aims to determine the value of Peak Hour Factor each respective lane, knowing the speed and the average density at the time of the Peak Hour, traffic characteristics determine the relationship of each lane by using fundamental diagrams. The research location is at Slamet Riyadi Street segment exactly in front of the stadium Sriwedari, Surakarta. Retrieving data using the video recorder carried out for 5 hours on Thursday, December 18, 2014 at the hour 9:05 to 14:05 pm and workmanship using PMB software from the Sony DCR SR47E. The analysis was conducted to find the value of PHF, speed and density during peak hours (Peak Hour), and put it into a mathematical model using the model Greenshield, Greenberg and Underwood. The results obtained by analysis of the value of PHF on the Lane I of 0.9088 and 0.9180 for both Lane II occurred at 9:50 to 10:50, while the value of PHF in Lane III, 0.9172 took place at 10:20 to 11:20. The value of the average room rate (Vs) and the density (D) of each lane during Peak Hour above is 42.39 km / hour and 18.73 smp / km (Lane I); 42.60 km / hour and 29.78 smp / km (Lane II); 34.20 km / hour and 22.71 smp / km (Lane III). Based on the analysis of fundamental diagram, the best model on the Lane I is by Vs = 53,9034 - 0,6333D with R2 = 0,3649; the best model on Lane II is by Vs=51,698.e-D/143,772with R2 = 0,3974, while the best model in Lane III is by Vs=6,8432.Ln(3276,207/D) with R2 = 0,2678. Keywords: PHF, space mean speed, average density, fundamental diagram.